Predicting 10-year survival after resection of colorectal liver metastases; an international study including biomarkers and perioperative treatment. (June 2022) - Buisman, Florian E.; Giardiello, Daniele; Kemeny, Nancy E.; Steyerberg, Ewout W.; Höppener, Diederik J.; Galjart, Boris; Nierop, Pieter M.H.; Balachandran, Vinod P.; Cercek, Andrea; Drebin, Jeffrey A.; Gönen, Mithat; Jarnagin, William R.; et al.
Abstract: Background: The aim of this study was to develop a prediction model for 10-year overall survival (OS) after resection of colorectal liver metastasis (CRLM) based on patient, tumour and treatment characteristics. Methods: Consecutive patients after complete resection of CRLM were included from two centres (1992–2019). A prediction model providing 10-year OS probabilities was developed using Cox regression analysis, including KRAS, BRAF and histopathological growth patterns. Discrimination and calibration were assessed using cross-validation. A web-based calculator was built to predict individual 10-year OS probabilities. Results: A total of 4112 patients were included. The estimated 10-year OS was 30% (95% CI 29–32). Fifteen patient, tumour and treatment characteristics were independent prognostic factors for 10-year OS; age, gender, location and nodal status of the primary tumour, disease-free interval, number and diameter of CRLM, preoperative CEA, resection margin, extrahepatic disease, KRAS and BRAF mutation status, histopathological growth patterns, perioperative systemic chemotherapy and hepatic arterial infusion pump chemotherapy. The discrimination at 10-years was 0.73 for both centres. A simplified risk score identified four risk groups with a 10-year OS of 57%, 38%, 24%, and 12%. Conclusions: Ten-year OS after resection of CRLM is best predicted with a model including 15 patient, tumour, and treatment characteristics. The web-based calculator can be used to inform patients. This model serves as a benchmark to determine the prognostic value of novel biomarkers. Highlights: A prediction model for a 10-year OS after colorectal liver metastasis resection was developed. Fifteen characteristics were independent factors (discrimination: 0.73). A risk score identified four groups with a 10-year OS of 57%, 38%, 24% and 12%.